2021
DOI: 10.1099/ijsem.0.005177
|View full text |Cite
|
Sign up to set email alerts
|

Arthrobacter cheniae and Arthrobacter frigidicola sp. nov., isolated from a glacier

Abstract: Two Gram-stain-positive, aerobic, rod-shaped, pink and light pink colony-forming bacteria, designated as Hz2T and MDT2-14T, respectively, were isolated from glacier cryoconite samples. Comparisons based on 16S rRNA gene sequences showed that strains Hz2T and MDT2-14T take Arthrobacter bussei KR32T and Arthrobacter zhaoguopingii J391T as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…UMCV2 was initially identified as Arthrobacter agilis since its 16S rRNA sequences showed a percent identity above 99.5% ( Valencia-Cantero et al, 2007 ). However, the 16S rRNA sequences of A. echini ( Lee et al, 2016 ), A. ruber ( Liu et al, 2018 ), A. bussei ( Flegler et al, 2020 ), A. sedimenti ( Lin et al, 2020 ), and A. cheniae ( Yang et al, 2021 ) also share a percent identity above 99.5% with the 16S rRNA gene of Arthrobacter sp. UMCV2.…”
Section: Discussionmentioning
confidence: 99%
“…UMCV2 was initially identified as Arthrobacter agilis since its 16S rRNA sequences showed a percent identity above 99.5% ( Valencia-Cantero et al, 2007 ). However, the 16S rRNA sequences of A. echini ( Lee et al, 2016 ), A. ruber ( Liu et al, 2018 ), A. bussei ( Flegler et al, 2020 ), A. sedimenti ( Lin et al, 2020 ), and A. cheniae ( Yang et al, 2021 ) also share a percent identity above 99.5% with the 16S rRNA gene of Arthrobacter sp. UMCV2.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic studies, supported by BLAST analyses of 16S rRNA gene sequences, indicated that the strains R5, ED-ICE-B-R1, and ED-ICE-B-G2 grouped together in the Arthrobacter clade, which was subdivided into two subgroups. One group comprised the red-pigmented R5 and ED-ICE-B-R1, which shared 99.53% of 16S rRNA gene sequence identity and were closely related to the red-pigmented Arthrobacter agilis strain IHBB 9979 [50] and Arthrobacter cheniae strain [51], respectively. The other group comprised the yellow-pigmented ED-ICE-B-G2, which was closely related to the yellow Antarctic Arthrobacter flavus strain IHBB 9551 [52] and shared 100% sequence identity with it (Figure 4).…”
Section: Actinobacteriamentioning
confidence: 99%
“…In the last decade, we isolated thousands of heterotrophic bacterial strains from the surface samples of glaciers in Western China, including some common taxa in the cryosphere, such as Arthrobacter, Cryobacterium, Flavobacterium, Polaromonas, Sphingomonas , and Janthinobacterium (Liu et al, 2015 ). Studies investigating these strains have promoted not only the discovery and validation of new species (Liu et al, 2019a , 2020b , 2021b ; Zhang et al, 2020 ; Yang et al, 2021 ) but also the understanding of novel functions (Liu et al, 2021a ) and evolutionary characteristics (Liu et al, 2020a ) of cold-adapted bacteria.…”
Section: Introductionmentioning
confidence: 99%